In-situ worn geometry effect over the surface roughness propagation during micro milling process - Nurul Farhana, Mohadzir; Ainur Munira, Rosli; Ahmad Shahir, Jamaludin; Mohd Nizar, Mhd Razali (Penerbit UMP, 2020)
High-precision miniaturized components for micro-machining operations has an increasingly demand for numerous developing sectors such as medical instrumentations, electronics components, computer manufacturing, aerospace and automotive engineering. Micro-milling has known as a flexible micro machining process and the most familiar micro mechanical machining method. Due to overcome a few difficulties in micro fabrication, micro milling is picked as an alternative way as it has potential and imperative for high accuracy machining. However, micro tools have low tool life as it is unpredictably and wear quickly. Furthermore, it also has tendency to break easily due to its micro size dimension.The study observe the behaviourof micro milling worn geometry during machiningand includes a non-conventional method to measure surface roughness resulted bymicro milling process in machining of mild steel AISI1045. The workpiece is prepared by using CNC milling machine with facing and slotting process. Then,the mild steel AISI1045 will undergo a machining process by a 1 mm size end milldiameter with different set of parameters which are of cutting speed. Once the best cutting speed is obtained based on surface roughness result, the tool life performance is teste.From the study, it is known that higher cutting speed gave better surface roughness, as limited for the study at 3000 rpm (7.53m/min). Meanwhile, higher cutting speed gave tool limited tool life, there is not much different with lower cutting speed for micro end milling process probably due to geometrical effect.